Gender and war : international and transitional justice perspectives / edited by Solange Mouthaan, Olga Jurasz. - Mouthaan, Solange; Jurasz, Olga (Intersentia, 2019)
This book explores and challenges common assumptions about gender, conflict, and post-conflict situations. It critically examines the gendered aspects of international and transitional justice processes by subverting traditional understandings of how wars are waged, the power dynamics involved, and the experiences of victims. The book also highlights the gendered stereotypes that underpin the (mis)perceptions about gender and war in order to reveal the multi-dimensional nature of modern conflicts and their aftermaths. Featuring contributions from academics in law, criminology, international relations, politics and psychology, as well as legal practitioners in the field, Gender and War offers a unique and multi-disciplinary insight into contemporary understandings of conflict and explores the potential for international and transitional justice processes to evolve in order to better acknowledge diverse and gendered experiences of modern conflicts. This book provides the reader with international and interdisciplinary perspectives on issues of international law, conflict, gender and transitional justice. Solange Mouthaan is Associate Professor of Law at the University of Warwick. Her research interests focus on the gendered experiences of children affected by armed conflict and the restrictive interpretation of international criminal law in this area. Olga Jurasz is a Senior Lecturer in the Law School at the Open University and works in the fields of international law, human rights, gender-based violence and gender and post-conflict reconstruction.